Cephalosporin-C production by free and immobilized cells of Cephalosporium acremonium in different modes of bioreactors - Mahapatra A.C.; Kundu K.; Nigam V.K.; Prasad M.V.; Kundu S. (My University, 2025)
Cephalosporin-C, a β-lactam antibiotic produced by the fungus Cephalosporium acremonium, was studied in batch and continuous modes using free and immobilized cells. Packed bed studies were also carried out using immobilized cells. The productivity of continuous stirred tank bioreactor was higher than that of the packed bed bioreactor. Cephalosporin-C concentration could be increased by recycle operation and use of optimum cell to carrier ratio. The immobilized cell system in stirred tank bioreactor was unstable due to the disruption of calcium alginate beads.